Chega - The new Portuguese far right - Carvalho, J. (2026)
In the late 2010s, the Portuguese immunity to the far right came to a sudden end at the 2019 general elections, after the election of Chega’s leader – André Ventura – to the Assembly of the Republic. In 2025, Chega became the second party with the largest parliamentary representation after securing 23 per cent of the vote and transformed the bipolar party system observed since 1974. This book is the first in-depth examination of the new Portuguese far-right party – Chega, whose ascension prompted a watershed in Portuguese politics. Overall, the Portuguese case study suggests that no country is immune to the emergence of far-right parties or to their quick normalisation in the national party system. Secondly, this investigation highlights the absence of a rule that fits all cases to understand far-right parties’ electoral breakthroughs or their consolidation at the national level. Drawing upon qualitative and quantitative data, the book's contents examine the new Portuguese far-right party according to different perspectives following the dichotomy of political supply and political demand. This book will appeal to undergraduate students, postgraduate researchers, and scholars interested in topics such as South European politics, the far right, populism, and comparative politics.